Multi-omics research on common allergens during the ripening of pollen and poplar flocs of Populus deltoides - Guo, Wei; Luo, Hui; Cao, Yi; Jiang, Ziyun; Liu, Hui; Zou, Jie; Sheng, Changle; Xi, Yilong (Frontiers in Plant Science, 2023)
Background: Populus deltoides is widely cultivated in China and produces a large number of pollen and catkins from March to June per year. Previous studies have found that the pollen of P. deltoides contains allergens. However, studies on the ripening mechanism of pollen/catkins and their common allergens are very limited. Methods: Proteomics and metabolomics were used to study the changes of proteins and metabolites in pollen and catkins of P. deltoides at different developmental stages. Allergenonline database was used to identify common allergens in pollen and catkins at different developmental stages. Westernblot (WB) was used to detect the cross-reaction between mature pollen and catkins. Results: In total, 1400 differently expressed proteins (DEPs) and 495 different metabolites (DMs) were identified from pollen and catkins at different developmental stages. KEGG enrichment analysis showed that DEPs in pollen and catkin were significantly enriched in ribosome and oxidative phosphorylation signaling pathways. The DMs in pollen are mainly involved in aminoacyl-tRNA biosynthesis and arginine biosynthesis, while the DMs in catkins are mainly involved in glyoxylate and dicarboxylate metabolism. Additionally, 72 common allergens were identified in pollen and catkins at different developmental stages. WB showed that there were distinct binding bands between 70 and 17KD at the two groups of allergens. Conclusions: A multitude of proteins and metabolites are closely related to the ripening of pollen and catkins of Populus deltoides, and there is an obvious cross-reaction between mature pollen and catkins.